Method for dosing solid urea (CO(NH2)2) and device for applying such a method - REICHERT, MARTINA; BARTSCH, LEONHARD (2009)
The metering solid urea (CO(NH 2) 2) for use as reducing agents for selective catalytic reaction (SCR) catalyst, comprises supplying the urea (3', 3") to a reactor by a metering unit, splitting up of the supplied urea in interaction with a heatable reactor element (1) of the reactor by thermolytic reacting under energy input into ammonia (NH 3) and isocyanic acid (HNCO), indirectly determining the energy input spent for the thermolytic reaction, and determining the supplied, split quantity of urea by the use of already determined energy input. The metering solid urea (CO(NH 2) 2) for use as reducing agents for selective catalytic reaction (SCR) catalyst, comprises supplying the urea (3', 3") to a reactor by a metering unit, splitting up of the supplied urea in interaction with a heatable reactor element (1) of the reactor by thermolytic reacting under energy input into ammonia (NH 3) and isocyanic acid (HNCO), indirectly determining the energy input spent for the thermolytic reaction, and determining the supplied, split quantity of urea by the use of already determined energy input. The temperature of reactor element is detected and the temperature drop of the reactor element is determined due to the thermolytic reaction of the urea. The spent energy input using this temperature drop is indirectly determined. The electrical resistance of reactor element is monitored, and the change of the resistance of the reactor element due to the temperature drop is determined. The spent energy input using this change of resistance is indirectly determined. The change of resistance is determined in such a way that the reactor element is attached to a constant voltage supply and the change of a current that flows through the reactor element is determined due to the change of resistance. For heating up of the reactor element, a heating device is intended, and a target temperature is given to this heating device for the split up of the supplied urea. The power requirement of the heating device necessary for the maintenance of the target temperature is determined, and the spent energy input using the power requirement is indirectly determined. The determined urea quantity is made available as an input signal. An independent claim is included for a device for metering solid urea for use as reducing agents for selective catalytic reaction catalyst.